Kelas Semiotik Nilai Pendidikan Karakter terhadap Masyarakat dalam Karya Raja Ali Haji - Isnaini Leo Shanty; Abdul Malik; Gatot Subroto (Jurnal Kiprah, 2019)
This paper is aimed to analyze semiotic classes of character education values to the people in the works of Raja Ali Haji. Five works of Raja Ali Haji, namely Syair Abdul Muluk, Gurindam Dua Belas, Thamarat al-Muhimmah, Tuhfat al-Nafis, and Syair Sinar Gemala Mestika Alam, were analyzed. In this study, four semiotic classes of character education values to the people were found: (1) rheumatic iconic qualisign, namely the quality of thoughts, feelings, traits, and attitudes attached to people who have that character, (2) rheumatic indexical sinsign, namely the quality of words and or behavior of someone that can be heard and or observed by others, (3) dicent indexical legisign, which is a sign that is meaningful information and refers to the subject of information based on certain norms, and (4) argument, namely the conclusions put forward by Raja Ali Haji is based on the truth he believes, namely the norms of Islamic teachings. Based on these findings, Raja Ali Haji’s works can be used as references for the development of character education material sourced from literary works.